Commission on Sustainable Agriculture and Climate Change informs diverse policy processes - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
How will we achieve food security as climate change approaches? To help answer this fundamental question, CCAFS convened the Commission on Sustainable Agriculture and Climate Change, with support from the Global Donor Platform for Rural Development. The Commission, consisting of thirteen senior scientists from diverse academic and institutional backgrounds, set out to provide an independent, interdisciplinary, and evidence-based assessment to be used by policymakers for addressing food security in the face of climate change.